Use of 13C-NMR as complementar identification tool in essential oil analysis. Issue 4 (1997) - Alencar Alencar, José Wilson José Wilson; de Vasconcelos Silva de Vasconcelos Silva, Maria Goretti Maria Goretti; Machado Machado, Maria Iracema Lacerda Maria Iracema Lacerda; Craveiro Craveiro, Afrânio Aragão Afrânio Aragão; de Abreu Matos de Abreu Matos, Francisco José Francisco José; de Abreu Magalhães de Abreu Magalhães, Ruy Ruy
Abstract : A program using 13 C-NMR data was developed to improve GC/MS identifications of chemical constituents in essential oils. Compiled data uses 2290 and 2370 chemical shifts of 229 monoterpenes and 158 sesquiterpenes, respectively, stored into two reference libraries. Each carbon atom was codified using rules that correlates its chemical shift with structural features of the carbon hybridization and vicinity.